Protecting wellbeing and resilience in BAME families and communities during a public health emergency (Hindi) - Solanke, Iyiola; ayisi, florence; Bernard, Claudia; Bhattacharyya, Gargi; Gupta, Anna; Kaur, Raminder; Lakhanpaul, Monica; Padmadas, Sabu; Rai, Shirin; Stokes, Maria (White Rose University Consortium, 2022)
Ignoring race, gender and class when tackling a pandemic can undermine not only wellbeing across Black, Asian and Minority Ethnic families and communities (BAME FC) but also their levels of trust in government. A framework to protect wellbeing and resilience in BAME FC during public health emergencies was developed by Co-POWeR to ensure that laws and guidance adopted are culturally competent.
Keywords: FOS: Sociology; FOS: Political science